Evidenzbasierte | evidenzinformierte Gesundheitskommunikation - Rossmann, Constanze (Medien + Gesundheit, 2018)
This volume discusses the relevance of evidence-based practice in health communication. Evidence-based medicine has largely established itself as a criterion of good practice, which means the conscientious, explicit and judicious use of the current best evidence in making decisions about healthcare. Similar attempts can be observed in health communication. However, health communication not only examines what kind of information is spread, but also how information has to be displayed in order for it to be perceived and processed adequately. The 19 chapters in this volume are partly theoretical and partly empirical illustrations of how evidence is reflected on in medicine, psychology and communication science. They deal, for example, with the criteria of evidence-based health communication, medical evidence in journalism and evidence-based campaigns.